2020
DOI: 10.1113/jp280118
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin markedly blunts cerebral perfusion and reactivity, with little cognitive consequence in healthy young and older adults

Abstract: Key points Cognitive function depends on adequate cerebrovascular perfusion and control. However, it is unknown whether acutely‐reduced cerebral blood flow (CBF) impairs cognition in healthy adults. In the present study, we used a placebo‐controlled, single‐blinded, randomized cross‐over design to test the hypothesis that acutely‐reduced CBF (using a pharmacological aid; indomethacin) would impair cognition in young and older healthy adults. At baseline, older adults had lower cognitive performance and CBF, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 89 publications
2
28
0
Order By: Relevance
“…However, the correlation between TCD CVR measures (average r = 0.43) taken was still much greater than the relationship of the TCD CVR measures to the CVR measures derived from PCA MRI (Supplementary Figure 5A, r = −0.19), which would have been expected to provide similar CVR measures. To fully be able to interpret these results it would be necessary to also assess test re-test reliability in the MRI CVR measures to try and disentangle if it is participant physiology (Shoemaker et al, 2020) or measurement technique that is driving this variability and is contributing to the lack of correlation between modalities. Nevertheless, the variability that we observed with the TCD-CVR is consistent with other studies that have reported CoV for this measure (Shoemaker et al, 2020) and/or examined its variability (Burley et al, 2020).…”
Section: Measurement Inaccuracy and Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the correlation between TCD CVR measures (average r = 0.43) taken was still much greater than the relationship of the TCD CVR measures to the CVR measures derived from PCA MRI (Supplementary Figure 5A, r = −0.19), which would have been expected to provide similar CVR measures. To fully be able to interpret these results it would be necessary to also assess test re-test reliability in the MRI CVR measures to try and disentangle if it is participant physiology (Shoemaker et al, 2020) or measurement technique that is driving this variability and is contributing to the lack of correlation between modalities. Nevertheless, the variability that we observed with the TCD-CVR is consistent with other studies that have reported CoV for this measure (Shoemaker et al, 2020) and/or examined its variability (Burley et al, 2020).…”
Section: Measurement Inaccuracy and Analysis Methodsmentioning
confidence: 99%
“…To fully be able to interpret these results it would be necessary to also assess test re-test reliability in the MRI CVR measures to try and disentangle if it is participant physiology (Shoemaker et al, 2020) or measurement technique that is driving this variability and is contributing to the lack of correlation between modalities. Nevertheless, the variability that we observed with the TCD-CVR is consistent with other studies that have reported CoV for this measure (Shoemaker et al, 2020) and/or examined its variability (Burley et al, 2020). Finally, the PCA MRI-derived flow measure of CVR in the MCA, which is not affected by the operator to the same extent as TCD acquisition, also did not correlate with the BOLD CVR metrics (Supplementary Figure 5B).…”
Section: Measurement Inaccuracy and Analysis Methodsmentioning
confidence: 99%
“…The novel findings reported by Shoemaker et al . (2020), demonstrate the profound resiliency of cognitive performance regardless of acute reductions in cerebral perfusion, importantly, in both young and older adults (Shoemaker et al . 2020).…”
Section: Cognitive Domains and Factors Affecting Cognitive Performancementioning
confidence: 99%
“…The results reported by Shoemaker et al . (2020) may be extended in several directions. First, older adults use neural compensation mechanisms by recruiting a set of brain areas to cope with the increasing attention load required to perform complex tasks (Ansado et al .…”
Section: Cognitive Domains and Factors Affecting Cognitive Performancementioning
confidence: 99%
See 1 more Smart Citation